Breastfeeding: Current knowledge, attitude, and practices among mothers in Mahbubnagar - Damireddy, Archana Reddy; Musali, Sumanth Reddy (Indian Journal of Child Health, 2020)
Background: Breastfeeding is an unequalled way of providing ideal food for the healthy growth and cognitive development of infants. Many sociodemographic factors play a major role in the exclusive breastfeeding (EBF) of the infants which needs to be thoroughly understood and analyzed to achieve the WHO recommended goal of EBF. Objectives: The objectives of the study were to describe the breastfeeding and complementary feeding practices in the first 2 years of life and to assess the influence of cultural and socioeconomic factors. Methodology: This prospective study was conducted between 2016 and 2017 in the immunization clinic and postnatal ward in a medical college of South India. A closed structured questionnaire in local language on knowledge, attitude, and practice regarding prelacteal feeds, breastfeeding, and complementary feeding based on the National Family Health Survey-4 was given to mothers of 500 children aged 0–24 months. Data collected included the baseline sociodemographic characteristics, time of initiation of breastfeeding, period of EBF, continued breastfeeding following introduction of complementary foods, and type of complementary foods introduced. Data were analyzed using appropriate statistical methods. Results: A total of 500 mothers were included in the study. The mean age of mothers was 20.8±2.75 years. Majority of the mothers (231 out of 500) started breastfeeding within 1 h (46.3%), whereas 98 mothers (19.6%) initiated breastfeeding as late as after 24 h. Colostrum was fed to babies in 84.16% of the cases. Prelacteal feeds were given in 24.13% of cases. EBF from day 1 was started in 72% of the mothers. Majority of the mothers started complementary foods only after 6 months. Conclusion: This study reveals the need for health promotion to focus on the benefits of EBF for both the infant and mother. Education should target new mothers and family members as they have a strong influence on child-rearing practices.